Personalizing Assessment: Dream or Nightmare? - Bennett, Randy E. (Educational measurement, issues and practice, 2024)
Over our field's 100‐year‐plus history, standardization has been a central assumption in test theory and practice. The concept's justification turns on leveling the playing field by presenting all examinees with putatively equivalent experiences. Until relatively recently, our field has accepted that justification almost without question. In this article, I present a case for standardization's antithesis, personalization. Interestingly, personalized assessment has important precedents within the measurement community. As intriguing are some of the divergent ways in which personalization might be realized in practice. Those ways, however, suggest a host of serious issues. Despite those issues, both moral obligation and survival imperative counsel persistence in trying to personalize assessment.